Myostatin inhibition: a potential performance enhancement strategy? - Fedoruk, M. N.; Rupert, J. L. (Scandinavian Journal of Medicine & Science in Sports, 2008)
A decade has passed since myostatin was first identified as a negative regulator of muscle growth. Since then, studies in both humans and animals have demonstrated that decreasing the levels of this growth factor or inhibiting its function can dramatically increase muscle size, and a number of therapeutic applications of myostatin inhibition to the treatment of myopathies and muscle atrophy have been proposed. As such treatments would be likely to also stimulate muscle growth in healthy individuals, there is a growing concern among anti-doping authorities that myostatin inhibitors may be among the next generation of ergogenic pharmaceuticals or even in the vanguard of "gene doping" technology. While the ability to stimulate muscle growth through myostatin inhibition is well documented, a growing body of evidence suggests such increases may not translate into an improvement in athletic performance. This article briefly reviews the function of this potent regulator of muscle development and explores the potential therapeutic uses, and potential ergogenic abuses, of myostatin manipulation.